PENGARUH PEMBERIAN MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. POSINDO (PERSERO) KANTOR CABANG PEKANBARU - Simbolon, Vera Helen; Andri, Seno (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This study aimed to determine the effect of motivation and discipline of work to employees performance at PT. Posindo (Persero) Branch Office Pekanbaru. Where the proposed two independent variables, namely the provision of motivation and discipline of work and the dependent variable is the performance of employees. Analysis of the data used by using spss. Results of analysis using multiple linear regression, t-test, and the test of determination (R2), and the F-test. So that the figures obtained R2 (R Square) of 0.673, or 67.3%. This shows that the percentage contribution of independent variables (motivation and discipline of work) on the dependent variable (performance of employees) amounted to 67.3% and strong relationships with a large award is 0.673. While the percentage of the remaining 32.7% (100% - 67.3%) influenced by other variables not included in this study variables.Keywords: Giving Motivation, Discipline Work, Employee Performance